THE RELATIONSHIP OF THE MORPHOLOGICAL FEATURES OF ADENOHYPOPHYSIS AND ADRENAL STILLBORN FROM HIV-INFECTED MOTHERS - Sherstiuk, S.A.; Sorokina, I.V. (World of Medicine and Biology, 2012)
In the group of stillbirths from HIV-infected women found a direct positive relationship between the functional state of the cells ofadenohypophysis and adrenal glands, which shows the morphofunctional state of adrenal suppression in the form of reduced diameter of adrenal cells, the density of cellular elements and an increase nuclei-cytoplasmicratio all areas of the cortex in response to a decrease in functional activity of thecells ofadenohypophysis that apparently due to prolonged exposure to the basic pathology of the parent on the body of the fetus in the antenatal period.
Keywords: anterior pituitary; adrenal glands; HIV infection; stillborn